2016
DOI: 10.5539/ies.v10n1p225
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Student’s Self-Directed-Learning Readiness and Academic Self-Efficacy and Achievement Motivation in Students

Abstract: Self-directed learning readiness to expand and enhance learning, This is an important goal of higher education, Besides his academic self-efficacy can be improved efficiency and Achievement Motivation, so understanding how to use these strategies by students is very important. Because the purpose this study is determination of relationship between students self-directed learning and academic self-efficacy and Achievement Motivation in Payamnoor students (2012-2013). In a correlation-descriptive study 322 bache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 3 publications
5
70
0
13
Order By: Relevance
“…The findings of the present study are also consistent with the results of the previous studies (Saeid & Eslaminejad, 2017;Kitsantas, Cheema, & Ware, 2011;Pajares & Miller, 1994), showing that self-confidence is critical for ies.ccsenet.org International Education Studies Vol. 10, No.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the present study are also consistent with the results of the previous studies (Saeid & Eslaminejad, 2017;Kitsantas, Cheema, & Ware, 2011;Pajares & Miller, 1994), showing that self-confidence is critical for ies.ccsenet.org International Education Studies Vol. 10, No.…”
Section: Discussionsupporting
confidence: 83%
“…The internal factors include achievement motivation and self-concept (Awan & Noureen, 2012;Kupari & Nissinen, 2013), self-directed learning readiness and academic self-efficacy (Saeid & Eslaminejad, 2017;Kitsantas, Cheema, & Ware, 2011), self-efficacy (Apollo, 2005 andShofiah 2002), and students' attitudes towards mathematics learning (Ismail & Awang, 2009). Natural intellectual ability is another internal factor that affects mathematics achievement (Ghufron & Risnawati, 2010;Retnaningsih, 1998;and Suri, 2000), but it is far from the only factor.…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…The desire for achievement and interest in learning make them trying independently to pursue the achievement they desire. The results of research by Saeid and Eslaminejad (2017) which showed that self-directed learning readiness correlated significantly with self-efficacy and achievement motivation of students in Payamnoor University.…”
Section: The Role Of Internal Factors On the Self Directed Learning Rmentioning
confidence: 99%
“…When the self-directed learning results of the main study are examined, it is seen that, majority of the students agreed with the statements but there were also many undecided students. Considering the fact that self-directed learning is about both internal characteristics of students and external factors, learning environments, as an external factor, should be designed so that students experience self-directed learning (Saeid & Eslaminejad, 2016). This could be accomplished by providing students with opportunities to study by themselves or collaboratively with others (Fahnoe & Mishra, 2013).…”
Section: Learning Processes For 21th Century Learningmentioning
confidence: 99%